Efecto de la fertilización con tres fuentes nitrogenadas en el crecimiento y fisiología del café (Coffea arabica L.) var. Castillo en el sector la Argelia Loja - Lamas Vidal, Ronal Alexis (2024)
Coffee production in Ecuador is one of the most represented agricultural crops due to its economic, social and ecological contribution to farmers. However, due to natural phenomena such as "El Niño", the reduction of arable land, the availability of labor and fertilization interact in determining the yield. In addition, nitrogen is the most limiting element in coffee growth and production since it is required in large quantities and its availability in soils is low; the lack of fertilization programs in the different phenological stages also limits yields. Therefore, the present research work was carried out in “La Argelia” area in Loja city belonging to the “San Sebastian” parish, which is located at an altitude of 2,133 meters above sea level, which was carried out from May to September 2023. The objective of this research was to determine the effect of fertilization with different nitrogen sources (Urea, ammonium nitrate and Nitrabor); using a dose of 200 kg/ha-1/year-1 of Nitrogen, soil analysis were performed; the morphological variables evaluated were: plant height, stem diameter, number of branches, leaf area and physiological variables: chlorophyll, density and stomatal index. For which a completely randomized block design (DBCA) was used, having an experimental unit of 10 plants with homogeneous characteristics; the data were analyzed by analysis of variance and a significance level with Tukey's test (p> 0.005), the evaluations were carried out monthly. The results indicate that at 120 DDA (Days After Application) the T1 treatment (Urea) obtained the best results in the variables height, leaf area, chlorophyll and density and stomatal index, on the other hand, for the number of branches and stem diameter it was indicated that the T3 (Nitrabor) and T2 (Ammonium nitrate) treatments are the ones that stand out. It can be seen that the nitrogen sources used were necessary to improve the morphological and physiological state of the coffee plants.